Difference of effectiveness between educational video media and PowerPoint on sedentary lifestyle on students’ knowledge - Sadida, Tsamarah Qaulan; Salawati, Trixie; Rokhani, Rokhani; Ibrahim, Mustefa; Jatmika, Septian Emma Dwi (Jurnal Cakrawala Promkes, 2024)
Living a sedentary lifestyle entails engaging in minimal physical activity and getting insufficient exercise. One of the common repercussions of sedentary habits among adolescents is obesity. With the onset of the COVID-19 pandemic, students often studied online, spending prolonged hours in front of computer screens. This shift to remote learning exacerbated the sedentary behavior already prevalent among adolescents, potentially worsening the risk of obesity and other associated health issues. To mitigate the detrimental effects of a sedentary lifestyle, this research aimed to enhance students' comprehension of relevant information on a sedentary lifestyle. A quasi-experimental pre-test and post-test design was used in this kind of study. Using the purposive sampling technique, the study sample consisted of 72 students from class X: 36 respondents from class X-1 were assigned to the instructional video media group, while 36 respondents from class X-2 were assigned to the PowerPoint group. A pre-test questionnaire was distributed to each group, followed by interventions and a post-test questionnaire. The Mann-Whitney test was used to analyze the data between groups, while the Wilcoxon test was used to analyze each group's data. After using PowerPoint and video media as an intervention, there was a significant difference in the respondents' knowledge level, with p values being the same (p value=0.000). The treatment group that used educational video media and the group that used PowerPoint media differed in effectiveness (p value=0.015). After receiving an intervention using a PowerPoint and video, the respondents' level of knowledge increased. Compared to PowerPoint presentations, educational videos are a more effective way to enhance understanding of inactive lifestyles. A remarkable opportunity exists to enhance adolescents' understanding of the importance of leading an active lifestyle by harnessing the potential of video media as an instrumental tool.